2005
DOI: 10.1017/s0265021505000426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epoetin alfa on blood transfusions and postoperative recovery in orthopaedic surgery

Abstract: Epoetin alfa increases perioperative Hb concentration in mild-to-moderately anaemic patients and thus reduces transfusion requirements. Patients receiving blood transfusions require a longer hospitalization than non-transfused patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 20 publications
(20 reference statements)
2
77
0
2
Order By: Relevance
“…The association between blood transfusion and hospital LOS in orthopaedic patients has been observed in the literature. Weber et al [21] found that time to discharge for patients undergoing orthopaedic surgery was longer in transfused than in non-transfused patients (12.9 ± 6.4 vs. 10.2 ± 5.0 days, p < 0.001). Others observed that allogeneic blood transfusion is associated with a significant increased hospital LOS after orthopaedic surgery [12,22].…”
Section: Hospital Length Of Staymentioning
confidence: 99%
“…The association between blood transfusion and hospital LOS in orthopaedic patients has been observed in the literature. Weber et al [21] found that time to discharge for patients undergoing orthopaedic surgery was longer in transfused than in non-transfused patients (12.9 ± 6.4 vs. 10.2 ± 5.0 days, p < 0.001). Others observed that allogeneic blood transfusion is associated with a significant increased hospital LOS after orthopaedic surgery [12,22].…”
Section: Hospital Length Of Staymentioning
confidence: 99%
“…A large number of studies have shown that perioperative transfusion of allogeneic blood is associated with increased morbidity and mortality. Poorer outcomes are ascribed to an increased risk of postoperative infection, 3-10 pulmonary complications, 8,11 greater number of ventilator days, 9,12 renal dysfunction requiring dialysis, 9 multi-organ dysfunction, 13 intensive care unit days, 10 increased length of stay, 14 and short-term mortality. 9,10 Risk-adjusted models have attempted to control for allogeneic transfusion as simply a marker for illness severity or complicated perioperative course.…”
Section: Perioperative Transfusion Of Allogeneic Blood Productsmentioning
confidence: 99%
“…37 Er y thropoiesis stimulating agents (ESAs). Erythropoietic agents, in particular epoetin alfa, have been used successfully to increase hemoglobin and decrease transfusion requirements [38][39][40][41][42][43] and are appropriate when used in advance of elective surgical procedures. Currently, epoetin alfa is the only ESA indicated for perioperative use to avoid allogeneic transfusions.…”
Section: Blood Safetymentioning
confidence: 99%